2008
DOI: 10.1101/gad.1640608
|View full text |Cite|
|
Sign up to set email alerts
|

The miR-200 family determines the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2

Abstract: [Keywords: Ovarian cancer; tumor progression; EMT; NCI60] Supplemental material is available at http://www.genesdev.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

127
1,938
6
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,066 publications
(2,081 citation statements)
references
References 46 publications
127
1,938
6
10
Order By: Relevance
“…A recent study demonstrated that the miRNA-200 family (miR-141, miR-200a, b, c, and miR-429) and miR-192/215 inhibit E-cadherin expression by targeting ZEB1 and ZEB2. [33][34][35][36][37] These previous reports suggest that solid-pseudopapillary neoplasm-specific downregulation of the miR-200 family and miR-192/215 targets components of the Wnt/b-catenin, Hedgehog, androgen receptor signaling pathways as well as genes associated with epithelial-mesenchymal transition. These effects ultimately result in decreased expression of epithelial markers.…”
Section: Discussionmentioning
confidence: 84%
“…A recent study demonstrated that the miRNA-200 family (miR-141, miR-200a, b, c, and miR-429) and miR-192/215 inhibit E-cadherin expression by targeting ZEB1 and ZEB2. [33][34][35][36][37] These previous reports suggest that solid-pseudopapillary neoplasm-specific downregulation of the miR-200 family and miR-192/215 targets components of the Wnt/b-catenin, Hedgehog, androgen receptor signaling pathways as well as genes associated with epithelial-mesenchymal transition. These effects ultimately result in decreased expression of epithelial markers.…”
Section: Discussionmentioning
confidence: 84%
“…miR-141 and miR-200a belong to the evolutionarily conserved miR-200 family. 17 The miR-200 family has been shown to determine the epithelial phenotype of cancer cells by targeting the E-cadherin repressors ZEB1 and ZEB2, 25 and a clinical study reveals that serum levels of miR-141 can be used as a biomaker of prostate cancer. 26 Abundant expression of miR-200a has been also shown in some prostate cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Most studies of molecular diagnosis of tissue of origin used messenger RNA (mRNA) profiling of tumor samples. 8,[13][14][15] MicroRNAs, 21-23-nucleotide-long functional RNAs, have an important function in tissue differentiation 16,17 and tumorigenesis, 18,19 and have highly tissue-specific expression patterns. [20][21][22] The unique expression profiles of microRNAs characteristic of each tissue and the malignancies arising in them can permit their accurate identification.…”
mentioning
confidence: 99%